MANAJEMEN PENGEMBANGAN KURIKULUM DALAM PENINGKATAN MUTU PENDIDIKAN DI MADRASAH TSANAWIYAH (MTs ) NURUL YAQIN WIDOROPAYUNG BESUKI SITUBONDO - Nur Faifatur R, M. Kurma; Arifin, Samsul; Sumarsi, Sumarsi (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2025)
This study aims to analyze curriculum development management in an effort to improve the quality of education in Madrasah Tsanawiyah (MTs) Nurul Yaqin Widoropayung, Besuki, Situbondo. The focus of this research includes planning, implementation, evaluation, and challenges faced in curriculum development. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of the madrasah head, teachers, and education personnel.The results showed that curriculum development management at MTs Nurul Yaqin is carried out through systematic stages, including identification of student needs, adjustment to the vision and mission of the madrasah, and integration of religious values and general knowledge. Curriculum implementation involves active participation from all stakeholders, including teachers and parents. Evaluation is conducted periodically to ensure the effectiveness of the curriculum and identify areas of improvement. However, the research also found some obstacles, such as limited human resources, inadequate infrastructure and lack of teacher training in understanding the latest curriculum. In conclusion, curriculum development management at MTs Nurul Yaqin has an important role in improving the quality of education. Recommendations from this study include improving teacher competence, strengthening collaboration between the madrasah and the community, and optimizing supporting facilities to support more effective and sustainable curriculum implementation.